Curcumin-infused lipid films for active and smart packaging: a sustainable solution - Abu Bakar, Ainaa Eliah; Wan Sulaiman, Wan Syibrah Hanisah; Othman, Rashidi (AIJR Publisher, 2025)
Packaging plays a vital role in preserving product quality, extending shelf life, and enhancing consumer appeal. In recent years, there has been a growing emphasis on innovation within the packaging industry to meet evolving consumer demands and environmental concerns. This chapter explores the integration of curcumin as a material selection in smart and active packaging, aiming to enhance both functionality and sustainability. Beginning with an overview of packaging materials, the discussion delves into the emergence of smart packaging, which incorporates technologies to monitor and improve product conditions. Active packaging is then introduced, highlighting its ability to actively interact with the packaged product to extend its shelf life or improve safety. The criteria for selecting active packaging materials are examined, emphasizing the importance of barrier properties and compatibility. Intelligent packaging is discussed as a subset of smart packaging, focusing on its ability to provide additional information or functionalities to consumers. The relationship between packaging and color perception and the use of colorants in packaging materials is explored. The chapter addresses concerns regarding synthetic colourants and their potential health implications, prompting the exploration of alternative options such as curcumin. Transitioning to specific product categories, the discussion encompasses both bar soap and liquid soap packaging, examining factors such as stability, foaming abilities, and the influence of surfactants. Within this context, the potential of curcumin as a material selection is investigated, considering its antimicrobial properties, antioxidant benefits, and biodegradability. Overall, this chapter provides a comprehensive overview of packaging innovations, culminating in a detailed examination of curcumin as a promising material for smart and active packaging applications. By embracing these innovations, the packaging industry can not only meet consumer expectations but also contribute to sustainable practices and environmental stewardship